Proposta de recomposição curricular para os anos iniciais da Rede Pública Municipal de Educação no Estado do Paraná: desafios do planejamento pedagógico - Scrivanti, Bruna Bellinato (2023)
This current work aims to propose a reflection on the Brazilian curriculum in the early years, specifically in the 5th year. For this purpose, a qualitative approach was adopted since it presentes the technique os content analysis, as to understand by Bardin (2011). Such an analysis approach is very relevant for this study that seeks to conduct a critical analysis of formal education documents, including the Base Nacional Comum Curricular (BNCC) and Parâmetros Curriculares Nacionais (PCNs), from a multidisciplinar perspective involving pedagogy and social science, in order to better undestand the implications of this situation for the quality of education in the contry. Since the region where the research was conducted was the state of Paraná, the study will also make a comparison with the oficial documents of this state, among which stands out the Currículo da Rede Estadual Paranaense (CREP). Considering the general objetive of this research, the central object of the study chosen was de pedagogical gap in this school period (1st to 5th grade) in the state os Paraná, more specifically in the city of Londrina. Thus, the theoretical framework includes the guidance of Félix Guattari and Gilles Deleuze philosophers who explore assemblages, experimentation and interpretation in life. Taking into account the nacional theoretical repertoire on education, the portulates of Paulo Freite were also used which aligns with the foreing philosophers. To provide na interesting counterpoint for the analysis, Bloom’s Taxonomy was also explored. Finally, it should be mentioned that the object os analysis was the textbook ‘Àpis Mais’ (2021) with na emphasis on Portuguese language actvities